... And other such stories - Umolu, Yesomi; Angiama, Sepake; Tavares, Paulo (Columbia Books on Architecture and the City, 2019)
Preface /Lori E. Lightfoot --Foreword /Todd Palmer --The city otherwise /Yesomi Umolu, Sepake Angiama, Paulo Tavares --Rights and reclamations.The racial question(ing) of justice /Denise Ferreira da Silva ;Excerpt from the case for reparations /Ta-Nehisi Coates ;Architecture of citizenship: São Paulo occupations /Paulo Tavares and Carmen Silva ;Alma de Bronze (bronze soul) /Virginia de Medeiros --Appearances and erasures.African space magicians /Lesley Lokko ;Excerpt from in the mecca: poems /Gwendolyn Brooks ;Decolonizing space: the case of #RhodesMustFall /Yesomi Umolu, Inam Kula, and Aviwe Mandyanda ;Appearances and (non)erasures: mapping confederate monuments and the racial conditionedness of liberation /Mario Gooden --No land beyond.Forest for the trees /Eduardo Kohn ;Adventure in Chinatown 1958 /Susie Silook ;Unceded territory: historicizing Vancouver /Sepake Angiama, cheyanne turions, and Vincent Tao ;Palatal geographies /Vivien Sansour --Common ground.The scale of commons and solidarity infrastructures /Pelin Tan ;Nourishing the root: transforming the urban ecologies of Chicago /Sepake Angiama and Emmanuel Pratt ;Concrete windows /Stephen Willats --Featured biennial contributors.Exhibiting contributors ;Publication contributors
Impressum: This book is published by the Chicago Architecture Biennial in association with Columbia Books on Architecture and the City on the occasion of the 2019 Biennial, "... and other such stories", curated by Yesomi Umolu, Sepake Angiama, and Paulo Tavares and on view from September 19, 2019, through January 5, 2020 (at the Chicago Cultural Center)
Includes bibliographical references
Keywords: Gesellschaft; Architektur; Soziologie; Städtebau; Chicago Architecture Biennial / (2019 / Chicago, Illinois); Architecture / Illinois / Chicago; Architecture, Modern / 21st century; Architecture, Modern; Illinois; Chicago; Ausstellungskatalog -- Chicago Cultural Center -- 19.09.2019-05.01.2020 -- Chicago, Ill.; Bildband